DOCKING OF CTX-M-9 GROUP OF ENZYMES WITH DRUGS AND INHIBITORS AND THEIR EVOLUTIONARY RELATIONSHIP - Kumar, Gandepalli Pratap (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Background: Among the type of ESBLs, CTX-M-type ESBLs represent a new and rapidly growing family of molecular class-A ESBLs. The prevalence of CTX-M-type ESBLs poses a serious threat to the clinical use of third generation cephalosporins for the treatment of severe infections. Objective: The objectives of the present study are computational study of CTX-M-9, 14 and 27 of blaCTX-M sequences. Based on resistance to organisms, docking of drugs (cefotaxime, cefixime and cefepime) as well as inhibitors (clavulanate, sulbactam and tazobactam) with CTX-M-9, 14 and 27 for the identification of amino acid residues crucial to the enzyme-drug and enzyme-inhibitor interaction. Method: Bioactivity analysis was done using Pubchem, and docking of drugs and inhibitors with CTX-M-9 group of enzymes were done using Schrodinger to identify the amino acid residues that are crucial for interaction. Phylogenetic analysis was constructed by Neighbor-Joining method for calculating minimum distance and bootstrapping values was done for 1000 replicates to obtain >70percent recombination. Results: Schrodinger analysis revealed the amino acid residues that interacted with CTX-M-9, 14 and 27 and they were found to be ASP 101, ASN 136, LYS 137, ASP 101, GLU 166, SER 130, ASN 132, THR 235, SER 237, and ASP 240 respectively. Among the drugs, cefotaxime, cefixime and among inhibitors clavulanic acid and tazobactam were found to interact with CTX-M-9, 14 and 27. Minimum distance obtained from Neighbor-Joining analysis was 0.02 evolutionary rate of divergence, and only two nodes connecting (CTX-M-3, 55 and CTX-M-9, 16, 51) of bootstrapping values revealed 100 and 88percent respectively, whereas other CTX-M-9 group of enzymes showed less than 70percent recombination. Conclusion: The current study revealed the amino acid residues crucial to ‘CTX-M-drug' and 'CTX-M-inhibitor' interactions among CTX-M-9 group of enzymes using different bioinformatics tools which would be useful for the development of a versatile CTX-M-inhibitor. Key words: ESBL, blaCTX-M, Docking, Neighbor-Joining.